Mapping the Path to Quality Early Childhood Education: Trends in Teacher Development in Indonesia - Istiana, Yuyun (Jurnal Caksana : Pendidikan Anak Usia Dini, 2024)
This study aims to map the trends in early childhood education (ECE) teacher development in Indonesia from 2020 to 2023 through a Systematic Literature Review of 51 nationally accredited academic articles. The findings reveal a clear shift in focus from basic pedagogical skills to digital literacy and the adoption of innovative pedagogical models aligned with the implementation of the Kurikulum Merdeka (Independent Curriculum). Moreover, the study identifies a significant geographic disparity, with most initiatives concentrated in the western and central regions of Indonesia, while eastern regions remain underserved in terms of professional development access. These findings underscore the urgent need to ensure equitable access to teacher training programs to realize inclusive and high-quality early childhood education in line with Sustainable Development Goal 4 (SDG 4). This research makes a meaningful contribution to evidence-based policymaking and strategic planning for strengthening the capacity of Indonesia’s ECE teaching workforce.